1971
DOI: 10.1083/jcb.48.2.314
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Inorganic Cations in Mouse Testis

Abstract: For localization of pyroantimonate-precipitable cations, mouse testes were fixed with a saturated aqueous solution of potassium pyroantimonate (pH about 9 .2, without addition of any conventional fixative), hardened with formaldehyde, and postosmicated . A good preservation of the cell membranes and over-all cell morphology is obtained as well as a consistent and reproducible localization of the insoluble antimonate salts of magnesium, calcium, and sodium . Four sites of prominent antimonate deposits are revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

1971
1971
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…Although inorganic ions are essential constituents of all animal and plant tissues, relatively little is yet known about their distribution as they exist in the living cell . Recently, the localization of the cations magnesium, calcium, and sodium (1,2), as well as that of inorganic orthophosphate anions (3,4), was revealed by electron microscope and microprobe analysis with the use of, respectively, potassium pyroantimonate and lead acetate aqueous solutions as fixatives .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although inorganic ions are essential constituents of all animal and plant tissues, relatively little is yet known about their distribution as they exist in the living cell . Recently, the localization of the cations magnesium, calcium, and sodium (1,2), as well as that of inorganic orthophosphate anions (3,4), was revealed by electron microscope and microprobe analysis with the use of, respectively, potassium pyroantimonate and lead acetate aqueous solutions as fixatives .…”
Section: Introductionmentioning
confidence: 99%
“…Although potassium pyroantimonate was first employed mixed with osmium tetroxide (5, 6)-a procedure basically followed by all subsequent investigators (7-23)-Tandler et al . (1,2) were the first to show that this salt alone behaves as a fixative and, furthermore, that the antimonate 830 precipitates contained magnesium and calcium in addition to sodium .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis provided evidence that the precipitates represented such inorganic cations as Ca, Mg or Na (Tandler et al, 1970;Kierszenbaum et al, 1971). In the present study, the subcellular distribution ofinorganic cations was studied in the vaginal epithelium of control and experimental rats.…”
mentioning
confidence: 97%
“…The vagina was dissected out and immersed in a large amount of fixative for 3 hr at room temperature (22\ s=deg\ C). The tissue was hardened in a formaldehyde\p=m-\potassiumpyroantimonate solution, washed with distilled water and post-osmicated as previously described (Kierszenbaum et al, 1971). After dehydration, the tissue was embedded in Maraglas epoxiresin.…”
mentioning
confidence: 99%
“…Since KOMNICK and KOMNICK (1963) first demonstrated that K-pyroantimonate formed electron opaque precipitate with tissue sodium, this technique has been widely used to detect certain cations such as Na, Ca and Mg in the tissue; control experiments are necessary because pyroantimonate is known to combine with several in Mytilus Smooth Muscle 253 cations (KOMNICK and KOMNICK, 1963;BULGER, 1969;TORACK and LAVALLE, 1970;SHIINA et al, 1970;TANDLER et al, 1970;KIERSZENBAUM et al, 1971;KLEIN et al, 1972;GARFIELD et al, 1972). LEGATO and LANGER (1969) and YAROM and MEIRI (1971 have suggested the possibility that the precipitate with PAO was due to Ca-pyroanti monate in heart and skeletal muscles, respectively.…”
Section: Identification Of the Precipitatementioning
confidence: 99%